Numerical Analysis and Experimental Verification of Resistance Additive Manufacturing - Suli Li; Kaiyue Ma; Chao Xu; Laixia Yang; Bingheng Lu (Crystals, 2022)
In recent years, scholars have proposed a metal wire forming method based on the Joule heat principle in order to improve the accuracy of additive manufacturing and reduce energy consumption and cost, but it is still in the theoretical stage. In this paper, a mathematical model of resistance additive manufacturing was established using finite element software, and the temperature variation of the melting process under different currents was analyzed. A suitable current range was preliminarily selected, and an experimental system was built. Through experimental study of the current and wire feeding speed, the influences of different process parameters on the forming appearance of the coating were analyzed. The results showed that the forming appearance was the best for Ti-6Al-4V titanium alloy wire with a diameter of 0.8 mm, when the current was 160 A, the voltage was 10 V, the wire feeding speed was 2.4 m/min, the workbench moving speed was 5 mm/s, and the gas flow rate was 0.7 m3/h. Finally, the process parameters were used for continuous single-channel multilayer printing, verified the feasibility of the process at the experimental level and provided reference data for the subsequent development of this technology.